La utilidad de la medición del grosor del segmento uterino inferior en pacientes con cicatriz uterina previa como predictor de sospecha clínica y/o rotura uterina en gestantes de 37 a 41 semanas en trabajo de parto fase latente de inicio espontaneo. Hospital Regional Docente de Trujillo. 2020 - 2022 - Anhuamán Ñique, Raúl (2020)
At present, there has been a high percentage of cesarean sections in our country in recent years, both in the public and private sectors, this leads to a greater number of women with a previous uterine scar in their second pregnancy and its termination due to Caesarean section. Some time ago it was an indication for an absolute cesarean section to have a previous cesarean section; however, today it is possible to attempt a vaginal delivery in the second if they wish. After a cesarean section, the study of the scar through the measurement of the thickness of the lower uterine segment by transvaginal ultrasound during the third trimester of pregnancy, would become a fundamental tool to identify those pregnant women with high risk, allowing us to reduce complications such as cases of uterine rupture in pregnant women with a previous cesarean section, which consider vaginal delivery as a means of termination of pregnancy.